FINANCIAL MANAGEMENT EFFORTS BASED ON LOCAL CULTURAL VALUES IN TRADITIONAL BUSINESSES IN SERANG, BANTEN PROVINCE - Ibrohim, Ibrohim; Surachman , Surachman (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze financial management efforts in traditional businesses in Serang City, Banten, which are influenced by local cultural values. The study employed a qualitative approach, with data collection techniques including in-depth interviews, participant observation, and documentation. Data analysis was conducted using NVivo 12. This study aims to identify themes, patterns, and interrelationships between financial literacy, financial management practices, and the influence of local culture on financial decision-making. The results show that business owners' financial literacy varies, but all implement simple cash recording as an adaptive mechanism. Informal financial management practices, such as simple budget planning and monthly evaluations, are consistent and effective. Local cultural values, including cooperation, deliberation, and mutual trust, facilitate capital collaboration, shared decision-making, and social accountability. Simple financial control strategies, combined with local cultural values ​​, enhance transparency, prevent conflict, and support business sustainability. This study confirms that traditional business financial management need not be complex; a combination of financial literacy, simple practices, and local cultural wisdom is sufficient to maintain business efficiency and financial stability.